2016
DOI: 10.1111/jpn.12533
|View full text |Cite
|
Sign up to set email alerts
|

Influence of graded levels of calcium and vitamin K in the diets of laying hens during the growing phase and their effects on the laying phase

Abstract: The aim of this study was to evaluate the effect of dietary supplementation of vitamin K (vit K) and Ca in the diets of laying hens on bone and blood parameters and performance during the growing phase and the effects on the laying phase up to 32 weeks. The study utilized 120 Hy-Line W-36 pullets in the growing phase (13-18 weeks), 80 laying hens in the production phase (20-32 weeks), distributed in a completely randomized design in a 2 × 5 factorial arrangement, two levels of Ca (0.8 and 1.4%) and five levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The cortical thickness and medullary bone diameter were then measured at the breaking point using digital Vernier calipers with an accuracy of ± 0.01 mm. Bone density was measured as bone weight to bone length ( Souza et al, 2017 ), modified to 100 g/mm index where higher bone density is indicated by higher weight to length index. The broken bones were later used to determine the femur ash content.…”
Section: Methodsmentioning
confidence: 99%
“…The cortical thickness and medullary bone diameter were then measured at the breaking point using digital Vernier calipers with an accuracy of ± 0.01 mm. Bone density was measured as bone weight to bone length ( Souza et al, 2017 ), modified to 100 g/mm index where higher bone density is indicated by higher weight to length index. The broken bones were later used to determine the femur ash content.…”
Section: Methodsmentioning
confidence: 99%
“…Bone diameter was measured at the middle of the shaft (horizontal plane). The Seedor index was calculated using the formula SI = bone weight (mg)/bone length (mm) to indicate the bone density (Souza et al, 2017). Percentage of dissected bones in relation to body weight was also calculated.…”
Section: Data Sample Collection and Laboratory Analysesmentioning
confidence: 99%
“…In turn, the humerus is pneumatized as a genetic adaptation to flight. Because these bones also differ in the degree of mineralization (Applegate and Liibum, 2002;Van Wyhe et al, 2012), the mechanical load acting on them, and the muscle attachment (Regmi et al, 2017), most studies concentrate on long bones (tibia, femur and humerus) as representative for skeletal health (Jendral et al, 2008;Van Wyhe et al, 2012;Souza et al, 2017).…”
mentioning
confidence: 99%
“…Vitamin K is involved in bone metabolism as a coenzyme of γ-carboxylase, enhancing bone formation, mineralization and the biosynthesis and activation of key bone proteins ( Zhang et al, 2003 ; Souza et al, 2017 ). OC, a marker of bone formation, is involved in bone mineralization ( Shen et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%